The Influence of Risk Management, Budget, and Performance in Realizing Good Governance - Lisnawati, Lisnawati; Ali, Hapzi (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
This scientific article is a literature study within the scope of financial management that covers the influence of risk management, budget, and performance in realizing good governance. The purpose of this article is to construct a hypothesis on the influence between variables that will be used in subsequent research. The research objects are online literature, Google Scholar, Mendeley, and other academic online media. This qualitative descriptive analysis research method includes library research sourced from e-books and open access e-journals. The results of this article are: 1) risk management affects Good Governance; 2) budget affects good governance; and 3) performance affects good governance.